Sombreado de fachada como alternativa a instalación de aire acondicionado Aplicación en edificio E.T.S. de la Universidad de Santiago de Compostela - BLANCO SILVA, Fernando (Observatorio Medioambiental, 2010)
The Protocol of Kyoto forces to the countries developed to limit his emissions of CO2 and other Greenhouse Gases, caused in his majority by the consumption of energy of origin fossil (oil, natural gas or coal) or in the production of electricity. In Spain this problem is more important because Spain does not have energetic resources. This paper makes an analysis of an experience realized in the University of Santiago of Compostela. This experience consists to realize an installation of shadow in the wall of the building Escuela Técnica Superior de Ingeniería like an alternative to an installation of air conditioned.